Intestinal Parasitic Infestations In Hiv Serpositive Children - BASAVARAJ,; SREEKANTHA,; SHEPUR.T .A,; SHASHIDHAR V NANDI,; AVINASH S S,; AMARESHWAR M, (International Journal of Pharma and Bio Sciences, 2012)
Objective: To study the prevalence of intestinal parasitic infestations in HIV seropositive children and to correlate these infestations with different immunological status and WHO clinical staging. Methods: Three consecutive samples of each 60 HIV seropositive children in the age group of 18 months to 15 years admitted in KIMS, Hubli,Karnataka, over a period of one year from 1st November2007 to 31st October 2008, were tested for intestinal parasites in the Microbiology department, KIMS, Hubli. Results: The overall prevalence of intestinal parasitic infestation found in this study was 35% (21/60 cases). Of 21 cases, 17 were seen in patients with severe immune suppression. Most of the intestinal parasitic infestations were seen in patients with diarrhea (16/28) cases compared to patients without diarrhea (5/32) cases. The most frequently detected intestinal parasite in this study was Balantidium Coli, followed by Ascaris lumbricoides, Trichuris trichura, Cryptosporidia, Hymenolepiasis nana, Strongyloides stercoralis, Enterobius vermicularis. One case of multiple intestinal parasitic infestations was also noted in this study. Conclusion: The present study highlights the magnitude of intestinal parasitic infestation HIV infected children. The prevalence was found to be significantly more in patients with diarrhea than without diarrhea. Most of the intestinal parasitic infestations were seen in severely immunosuppressed children. However, parasites were also observed in other immune suppression group. So intestinal parasitic infestation should be suspected in all HIV seropositive children particularly with diarrhea and severe immune suppression.